Critical remark on the solar cell concept with a metal intermediate band - Dittrich, Thomas (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2013)
The solar cell concept with a metal intermediate band promises energy conversion efficiencies above the Shockley - Queisser limit. However, ideal absorption has to be taken into account for thermal generation including the metal intermediate band, and charge-selective contacts can only probe chemical potentials in the photovoltaic absorber. Solar cells with a metal intermediate band cannot exceed the Shockley -Queisser limit.